What are enterprise blockchains? - Loukides, Michael Kosta (O'Reilly Media, 2018)
Interest in the blockchain ledger that supports Bitcoin and other cryptocurrencies is rising in the tech community, particularly among planners in the enterprise. How will enterprise companies use blockchains? Many possibilities exist, such as recent efforts by Maersk and IBM to build a network for tracking container shipments that will integrate thousands of businesses. In this ebook, author Mike Loukides examines how the enterprise might work with blockchains in a way that takes real advantage of the technology. Managers and strategists will start with the basics and then examine several issues that could arise when building a blockchain. You'll also learn about current blockchain projects for digital identity, power distribution, shipping, labor, the IoT, healthcare, education, and games. Learn how blockchains provide strong guarantees about accuracy and consistency, even when shared by untrusted participants Understand Bitcoin's intricate process for adding new blocks to its chain Examine how blockchains are able to maintain privacy and anonymity Learn about smart contracts--also known as decentralized applications or Dapps Explore enterprise blockchain providers, hosting companies, tools vendors, platform and framework providers, and consultancies Review a list of questions you need to consider when looking into a blockchain deployment.